A literature review: analyzing barriers hindering the implementation of self-regulated learning in science classrooms - Del Mario, Jayme; Tran, Hong (Frontiers in Education, 2024)
Self-regulated learning is a goal-directed process in which learners are metacognitively, motivationally, and behaviorally active participants in their learning process. Although studies have shown self-regulated learning is critical for success in academic learning and beyond; many students do not use self-regulated learning strategies to drive their science learning. To better understand the circumstances surrounding this unfortunate situation, this literature review reports on 15 studies related to barriers that hinder science teachers from enacting self-regulated learning. In this review, we discuss the role of self-regulated learning, then we emphasize the theoretical frameworks, and examine the barriers. Findings from this study revealed six primary barriers: scarcity of time, disregards within the curriculum and assessments, lack of training, opposing teacher views, lack of resources, and students’ resistance toward self-regulated learning. Thus, with the support of current literature surrounding remedying these obstacles, we conclude our review by qualitatively analyzing the relationships between the barriers and suggest approaches toward overcoming them.